Pengaruh Latihan Single Leg Bound dan Split Jump Terhadap Kemampuan Servis Punggung Sepak Takraw - Aditya Ilham (Journal of Physical Activity and Sports (JPAS), 2021)
The Effect of Single Leg Bound and Split Jump Exercises on the Back Service Ability of the Sepak Takraw Klub Academy Sepak Takraw Foundation (ASTF) Dukuhseti". Faculty of Social and Sport Sciences Education, PGRI University Semarang in 2020. This research was motivated by the unfavorable condition of the ASTF Dukuhseti club's Sepak takraw training, this is seen from there are still many athletes who have not mastered the technique of doing tekong or back service properly and many do not cross the net while serving. In addition, the Tekong pedestal is still weak to support when serving, so that the footstool steps on or comes out of the service circle. The purpose of this study was to determine how the effect of single leg bound and split jump training on the back service ability of the Sepak Takraw Club Academy Sepak Takraw Foundation (ASTF) Dukuhseti. This research method is an experimental research method with the design "two groups prestest-posttest design". Group A was treated with single leg bound exercise and Group B was treated with split jump exercise. The population of this study were athletes from the ASTF Dukuhseti club aged 12-20 years. The sample used was all 16 athletes of the ASTF Dukuhseti club tekong club, the samples were taken using purposive sampling technique and group division using the original pairing technique. The instrument used in this study was back service. The data analysis technique used the Kolmogorov-Smirno normality test and the homogeneity test, then the final analysis used the t-test. The results of this study, the single leg bound exercise t-test showed the value = -13,981 with sig. (2-tailed) 0.000 <0.05 while the split jump exercise t-test shows the value of t = -8.275 sig. (2-tailed) 0.000 <0.05. So that single leg bound training is effective for improving the ability to serve takraw backs. The conclusion from this study is that the single leg bound training method is more effective for improving the ability of the back service of the Sepak Takraw to the ASTF Dukuhseti club athletes, compared to the split jump exercise, this is evidenced by the data obtained by the increase in single leg bound training by 41.25% and increased training. split jump of 18.75% or (41.25%> 18.75%). The suggestion that can be given to the ASTF Dukuhseti club's Sepak takraw athletes is to always try to practice improving the service ability of the Sepak Takraw back so that they can achieve achievements.               Abstrak Aditya Ilham. “Pengaruh Latihan Single Leg Bound Dan Split Jump Terhadap Kemampuan Servis Punggung Sepak Takraw Klub Academy Sepak Takraw Foundation (ASTF) Dukuhseti”. Fakultas Pendidikan Ilmu Pengetahuan Sosial dan Keolahragaan, Universitas PGRI Semarang Tahun 2020. Penelitian ini dilatarbelakangi oleh kondisi latihan sepak takraw klub ASTF Dukuhseti kurang baik, hal ini dilihat dari masih banyak atlet yang belum menguasai teknik melakukan tekong atau servis punggung dengan baik dan banyak yang tidak sampai melewati net saat melakukan servis. Selain itu juga kaki  tumpu  tekong masih  lemah  untuk  menumpu saat melakukan servis, sehingga  kaki  tumpu  menginjak atau keluar dari lingkaran servis. Tujuan penelitian ini adalah untuk mengetahui bagaimana pengaruh latihan single leg bound dan split jump terhadap kemampuan servis punggung sepak takraw klub Academy Sepak Takraw Foundation (ASTF) Dukuhseti. Metode penelitian ini merupakan metode penelitian eksperimen dengan desain “two groups prestest-posttest design”. Grup A diberi perlakuan latihan single leg bound dan Grup B diberi perlakuan latihan split jump. Populasi penelitian ini adalah atlet tekong klub ASTF Dukuhseti usia 12-20 tahun. Sampel yang digunakan adalah keseluruhan atlet tekong klub ASTF Dukuhseti yang berjumlah 16 atlet, pengambilan sampel menggunakan teknik purposive sampling dan pembagian kelompok menggunakan teknik oridinal pairing. Instrument yang digunakan dalam penelitian ini yaitu servis punggung. Teknik analisis data menggunakan uji normalitas kolmogorov-smirno dan uji homogenitas, selanjutnya analisis akhir menggunakan uji t-test. Hasil dari penelitian ini, pada uji t-test latihan single leg bound menunjukkan nilait = -13,981 dengan sig. (2-tailed) 0,000 < 0,05 sedangkan pada uji t-test latihan split jump menunjukkan nilai t = -8,275 sig. (2-tailed) 0,000 < 0,05. Sehingga latihan single leg bound efektif untuk meningkatkan kemampuan servis punggung sepak takraw. Simpulan dari penelitian ini adalah metode latihan single leg bound lebih efektif untuk meningkatkan kemampuan servis punggung sepak takraw pada atlet tekong klub ASTF Dukuhseti, dibanding latihan split jump,hal tersebut dibuktikan dengan diperolehnya data peningkatan latihan single leg bound sebesar 41,25% dan peningkatan latihan split jump sebesar 18,75% atau (41,25%>18,75%). Saran yang dapat diberikan bagi atlet sepak takraw klub ASTF Dukuhseti agar selalu berusaha berlatih meningkatkan kemampuan servis punggung sepak takraw sehingga dapat meraih prestasi.